The Phenomenon of Buddhist Ethics in Economic Implementation in Indonesia - Kresno Budoyoa Partono Nyanasuryanadi; Suherman Suherman (Eduvest - Journal of Universal Studies, 2025)
Economic success is often measured by material possessions, but obtaining these materials can sometimes harm others and neglect their needs. This was seen in the 2008 milk factory incident in China and the manipulation of TPS financial reports in Indonesia in 2019. Buddhism offers an alternative approach that emphasizes ethical and spiritual values in all aspects of life, including business. Using a phenomenological approach, this study explores how Buddhist entrepreneurs in Indonesia apply Buddhist ethics and economics in their business practices. Two themes emerged from the research: business ethics and Buddhist economic interpretation. These two themes can be elaborate into 6 (six) subthemes. While similarities can be found between Buddhist and modern economic theories, Buddhist entrepreneurs still face challenges in implementing their values in practice. Apart following the regulations, traditions and  business influences along with social interaction that apply within the society of a region country. The research is not to prove whose implementation is most correct.